WTO breakthrough on stockpiles : sustaining food security - Jonatan, A Lassa (2015)
The recent WTO agreement, finally concluded after the resolution of an impasse on food stockholding, has been hailed as a landmark for international trade. The deal however also holds great significance for global food security. However, some important concerns remain.